О задачах группового преследования при интегральных ограничениях на управления игроков. I - Саматов, Б.Т. (Кибернетика и системный анализ, 2013)
Вивчаються задачі групового переслідування для лінійних диференціальних ігор з інтегральними обмеженнями. При аналізі цих задач основним інструментом є метод розв’язувальних функцій Чикрія. Запропоновано конструкцію побудови розв’язувальної функції, що обгрунтовує правило паралельного зближення гравців, тобто П-стратегію для переслідувачів. Отримано нові достатні умови розв’язності для задач групового переслідування. Як приклад розглянуто два класи ігор: контрольний приклад Понтрягіна та групове переслідування з простим рухом гравців для випадку «l-упіймання». The paper presents a prediction method that uses a parallel-hierarchical (PH) network. This work studies problems of group pursuit for linear differential games with integral constraints on controls of players. The problems were solved on the basis of the method of resolving functions proposed by Chikrii. The proposed method substantiates the parallel approach strategy, i.e., the Ï-strategy. New sufficient solvability conditions are obtained for problems of group pursuit. Theoretical facts are illustrated be giving examples of two interesting classes of problems, namely, the Pontryagin control example and a group pursuit with a simple movement for the of case “l-catch.”